Oral Health and Periodontal Tissues Condition Assessement Among Interns and Residents of the Department of the Therapeutic Stomatology of the I.M. Sechenovfirst Moscow State Medical University - O. I. Admakin; I. M. Makeeva; K. S. Babina; T. S. Ivanova (Сеченовский вестник, 2015)
The paper presents the examination results of 46 interns and 10 residents on the subject of hygienic condition of the oral cavity and the results of the survey in the same groups. After the data processing the percentages of the examines with excellent and good hygiene have matched and have reached 80%. A direct strong and reliable correlation has been indicated between PMA/ Muhlemann indices (r=0,8). The collation of the received results with the results of 2012 research (prof. Makeeva I. M., Babina K.S.) allowed to conclude that during the studies at the university the motivation of the students increases and oral hygiene skills accumulate.